Fiber-Optic Chemical Sensors and Fiber-Optic Bio-Sensors - Pospíšilová, Marie; Kuncová, Gabriela; Trögl, Josef (Sensors (Basel, Switzerland), 2015)
This review summarizes principles and current stage of development of fiber-optic chemical sensors (FOCS) and biosensors (FOBS). Fiber optic sensor (FOS) systems use the ability of optical fibers (OF) to guide the light in the spectral range from ultraviolet (UV) (180 nm) up to middle infrared (IR) (10 μm) and modulation of guided light by the parameters of the surrounding environment of the OF core. The introduction of OF in the sensor systems has brought advantages such as measurement in flammable and explosive environments, immunity to electrical noises, miniaturization, geometrical flexibility, measurement of small sample volumes, remote sensing in inaccessible sites or harsh environments and multi-sensing. The review comprises briefly the theory of OF elaborated for sensors, techniques of fabrications and analytical results reached with fiber-optic chemical and biological sensors.
Keywords: chemical sensor; Equipment Design; Optical Fibers; biosenzitivní techniky; technologie optických vláken; Biological Assay; Chemistry Techniques, Analytical; fiber-optic sensor; immobilization of biologicals; biotest; design vybavení; enzymatic sensor; Fiber Optic Technology; Biosensing Techniques; optická vlákna; lidé; whole cell biosensor; chemické techniky analytické; Humans; tapered optical fiber